2021
DOI: 10.3390/md19050239
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Anti-Lipopolysaccharide Factor Isoform 3 in Chlamydomonas reinhardtii Showing High Antimicrobial Activity

Abstract: Antimicrobial peptides are a class of proteins with antibacterial functions. In this study, the anti-lipopolysaccharide factor isoform 3 gene (ALFPm3), encoding an antimicrobial peptide from Penaeus monodon with a super activity was expressed in Chlamydomonas reinhardtii, which would develop a microalga strain that can be used for the antimicrobial peptide production. To construct the expression cluster, namely pH2A-Pm3, the codon optimized ALFPm3 gene was fused with the ble reporter by 2A peptide and inserted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Chlamydomonas reinhardtii has proven to be an effective platform for recombinant protein/peptide production (Reyes-Barrera et al 2021 ; Li et al 2021 ; Jiang et al 2021 ). In this study, the IL29 protein was first expressed in an algal expression system.…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydomonas reinhardtii has proven to be an effective platform for recombinant protein/peptide production (Reyes-Barrera et al 2021 ; Li et al 2021 ; Jiang et al 2021 ). In this study, the IL29 protein was first expressed in an algal expression system.…”
Section: Discussionmentioning
confidence: 99%
“…To produce target carotenoids in E. coli , plasmids pET-DsLcyb1 and pET-CrtY were transferred into the chemical competent cell of lycopene-producing E. coli using heat-shock method [ 25 ]. To produce target carotenoids in C. reinhardtii , the plasmid pDb-CrtY was transferred into algal cells using glass-bead method with few modifications [ 26 ]. The algal transformation process was performed as described, with additional information that NotI was used to linearize plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the presence of the protein ALF Pm 3 in T-JaA and T-JcA, the total proteins in cells and the secretory protein in culture supernatant were extracted and subjected to immunoblot analysis. Algal cells were pelleted by centrifugation and total intracellular proteins were extracted based on the reference literature [ 9 ]. The extracellular protein from culture medium was extracted as follows: the culture medium was collected by centrifugation and then freeze dried.…”
Section: Methodsmentioning
confidence: 99%
“…As one cluster of the known AMPs, anti-lipopolysaccharide factors (ALF) firstly found in Limulus polyphemus displayed high antibacterial activity [ 7 ]. In recent years, it was reported that the anti-lipopolysaccharide factor 3 (ALF Pm 3) from Penaeus monodon with a lipopolysaccharide binding domain (LBD) had strong antibacterial activity against common aquaculture pathogenic bacteria, such as Vibrio harveyi , Vibrio parahaemolyticus , and Staphylococcus aureus , at a very low concentration (0.77 µM), showing its potential for application in the aquaculture industry [ 8 , 9 , 10 ]. ALF Pm 3 is commonly produced via genetic engineering due to its low yield from natural sources.…”
Section: Introductionmentioning
confidence: 99%